Job Satisfaction and Career Development in the Field of Library and Information Science - Jay Singh (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2023)
As a librarian a very few jobs were posted on online portals, it was supposed that this job does not required a lot of man power, but now a days leading research and higher academic need require a well equipped library and professional library staff. But library is not an independent unit as it need a lot of administration and communication with the management regarding fund and requirements. So rather this is a few occupied jobs in many ways but this job also needs a satisfaction towards the librarian post. Keywords. Satisfaction, management, administration, career, librarian